Effects on Polo-like Kinase 1 Polo-box Domain Binding Affinities of Peptides Incurred by Structural Variation at the Phosphoamino Acid Position - Qian, Wenjian (2012)
Protein-protein interactions (PPIs) mediated by the polo-box domain (PBD) of polo-like kinase 1 (Plk1) serve important roles in cell proliferation. Critical elements in the high affinity recognition of peptides and proteins by PBD are derived from pThr/pSer-residues in the binding ligands. However, there has been little examination of pThr/pSer mimetics within a PBD context. Our current paper compares the abilities of a variety of amino acid residues and derivatives to serve as pThr/pSer replacements by exploring the role of methyl functionality at the pThr β–position and by replacing the phosphoryl group by phosphonic acid, sulfonic acid and carboxylic acids. This work sheds new light on structure activity relationships for PBD recognition of phosphoamino acid mimetics.